Medium-throughput production of recombinant human proteins: Protein production in E. Coli - Burgess-Brown, N; Mahajan, P; Strain-Damerell, C; Gileadi, O; Gräslund, S (2014)
In Chapter 4 we described the SGC process for generating multiple constructs of truncated versions of each protein using LIC. In this chapter we provide a step-by-step procedure of our E. coli system for test expressing intracellular (soluble) proteins in a 96-well format that enables us to identify which proteins or truncated versions are expressed in a soluble and stable form suitable for structural studies. In addition, we detail the process for scaling up cultures for large-scale protein purification. This level of production is required to obtain sufficient quantities (i.e., milligram amounts) of protein for further characterization and/or crystallization experiments. Our standard process is purification by immobilized metal affinity chromatography (IMAC) using nickel resin followed by size exclusion chromatography (SEC), with additional procedures arising from the complexity of the protein itself. © 2014 Springer Science+Business Media, LLC.